CONCERNING THE LEGAL REGULATION OF FORENSIC PROCEDURES INCLUDING INITIAL BODY EXAMINATION AT THE SCENE AND FORENSIC AUTOPSY - Yu. Dubyagin; O. Dubyagina; V. Seryakov (Теория и практика судебной экспертизы, 2014)
Issues surrounding the interaction of criminal investigator with the forensic team in thecourse of various forensic procedures is discussed, with forensic autopsy viewed as aprocedural extention of the death investigation performed at the Medical Examiner'sOffice.